PENERAPAN METODE SINGLE MINUTE EXCHANGE OF DIE (SMED) UNTUK MENURUNKAN WAKTU SETUP MESIN DI PT.XYZ - Dwie Achmad Basyar (2022)
PT. XYZ is a market player in the pharmaceutical industry, particularly pharmaceuticals in the manufacturing of solid, semi-solid, and repacking products. This industry competes to create competitive products that can meet market needs. Based on direct field observations and interviews in 2021, there are problems with the setup time difference between a series of solid manufacturing machines so the outputs result are not optimal. The purpose of this research is to analyze the activities carried out on machine setup activities, as well as to reduce setup time using the Single Minute Exchange of Die (SMED) method to obtain optimal output results in the solid process. The research was supported by the Pareto Diagram, Process Flow Map, Time Study, SMED, Fishbone Diagram, and simulation using Arena Simulation Software. The results obtained in this study indicate that the standard time difference for the tableting machine setup is 34.9 minutes or 2097 seconds with a percentage reduction value of 18.7%. Meanwhile, for the primary packing line 3 machine, the standard setup time difference is 33.1 minutes or 1985 seconds with a percentage reduction of 21.4%. The actual production value is an average of 1267 large boxes/month to 1508 large boxes/month based on the proposed simulation difference, the difference is obtained by 241 large boxes/month and an average increase of 19.02% per month.